RNA viruses, M satellites, chromosomal killer genes, and killer/nonkiller phenotypes in the 100-genomes S. cerevisiae strains - Vijayraghavan, Sriram; Kozmin, Stanislav G; Strope, Pooja K; Skelly, Daniel A; Magwene, Paul M; Dietrich, Fred S; McCusker, John H (G3 : genes - genomes - genetics, 2023)
Abstract We characterized previously identified RNA viruses (L-A, L-BC, 20S, and 23S), L-A–dependent M satellites (M1, M2, M28, and Mlus), and M satellite–dependent killer phenotypes in the Saccharomyces cerevisiae 100-genomes genetic resource population. L-BC was present in all strains, albeit in 2 distinct levels, L-BChi and L-BClo; the L-BC level is associated with the L-BC genotype. L-BChi, L-A, 20S, 23S, M1, M2, and Mlus (M28 was absent) were in fewer strains than the similarly inherited 2µ plasmid. Novel L-A–dependent phenotypes were identified. Ten M+ strains exhibited M satellite–dependent killing (K+) of at least 1 of the naturally M0 and cured M0 derivatives of the 100-genomes strains; in these M0 strains, sensitivities to K1+, K2+, and K28+ strains varied. Finally, to complement our M satellite–encoded killer toxin analysis, we assembled the chromosomal KHS1 and KHR1 killer genes and used naturally M0 and cured M0 derivatives of the 100-genomes strains to assess and characterize the chromosomal killer phenotypes.